2021
DOI: 10.1177/00910260211012713
|View full text |Cite
|
Sign up to set email alerts
|

Does Grit Matter to Employees’ Quality of Work Life and Quality of Life? The Case of the Korean Public Sector

Abstract: To ensure the quality of the work done in the Korean career civil service system (which is characterized by stability, such as lifelong job security), the public sector must use methods to motivate their employees and improve their performance in the long run. In this study, we propose that grit, as a type of work motivation, can boost employee well-being (i.e., job satisfaction, job stress) and organizational outcomes (i.e., organizational commitment, performance). Therefore, the main objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
1
8
0
3
Order By: Relevance
“…A research model was also proposed to provide insights into the relationship between the variables mentioned earlier in this study (grit, feedback, person-organization fit, creativity). This research focus was triggered by prior emphases on grit and other organization outcome variables (Jordan et al, 2019a;Kim and Lee, 2022) and the limited research on the role of grit in performance (i.e., grit and employee creativity; Crede, 2018). The study confirmed that grit is associated with creativity as well as grit positive relationship with work engagement.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A research model was also proposed to provide insights into the relationship between the variables mentioned earlier in this study (grit, feedback, person-organization fit, creativity). This research focus was triggered by prior emphases on grit and other organization outcome variables (Jordan et al, 2019a;Kim and Lee, 2022) and the limited research on the role of grit in performance (i.e., grit and employee creativity; Crede, 2018). The study confirmed that grit is associated with creativity as well as grit positive relationship with work engagement.…”
Section: Discussionmentioning
confidence: 71%
“…In the same vein, work engagement fully mediates the association between job resources (variety, control, and feedback) and behaviors that are proactive (Salanova and Schaufeli, 2008). Some past studies also identified a positive relationship between employees' grit and work engagement (Von Culin et al, 2014;Suzuki et al, 2015;Kim and Lee, 2022). Similarly, other previous studies affirmed the link between work engagement and employees' creativity in the workplace (Bakker and Xanthopoulou, 2013;Asif et al, 2019;Bakker et al, 2020).…”
Section: The Mediating Role Of Work Engagementmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, spillover might satisfy or dissatisfy individuals improving or compromising their quality of life (Casper et al, 2018). Kim and Lee (2021) found that grit has an impact on people's quality of life. As a two-edged sword, higher expectations boost employees' capabilities while also impacting their work-life balance (Yang et al, 2022).…”
Section: Dual Outcomes Of Gritty Leadershipmentioning
confidence: 99%
“…Jika banyak pegawai yang memiliki kepuasan kerja yang rendah, tentu akan berdampak secara negatif pada perusahaan. Pegawai mengalami kepuasan kerja yang rendah, maka produktivitas akan berkurang dan dapat menyebabkan burnout (Kim & Lee, 2022;Kwon, 2021;Moen & Olsen, 2020). Hal ini tentu akan berdampak pada perusahaan seperti tingginya ketidak hadiran pegawai dan tingginya turnover yang menyebabkan produktivitas perusahaan menjadi tidak optimal dan kurangnya efektivitas kinerja pada perusahaan (Javed et al, 2014;Sellers et al, 2019).…”
unclassified